1991
DOI: 10.34194/bullggu.v161.6717
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology, evolution and systematics of Early Palaeozoic univalved molluscs

Abstract: This bulletin contains two papers describing aspects of the functional morphology and systematics of Early Palaeozoic untorted molluscs and bellerophontacean gastropods. A brief discussion of the potential role in early molluscan evolution of articulated halkieriids recently discovered from the Lower Cambrian of North Greenland forms an introduction to the volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Muscle scars are grouped into a horseshoe-shape on the dorsal surface; the apex lies outside of this ring in some forms and may overhang the anterior shell margin; in other forms, the apex is sub-central in position. Peel (1991b) recognised three orders, reflecting three different morphological groups, the Tryblidiida Lemche 1957 typically with a pilinaform shell, the Cyrtonellida Horný, 1963 with a planispirally coiled shell, and the Hypseloconida Peel 1991b with a tall cone-shaped shell. The Tergomya is equivalent to the sub-class Tergomya of Horný (1965a, b) and is also very similar to the Tryblidiida of Wingstrand (1985); Tryblidia is broadly used interchangeably with Monoplacophora in neontological usage (e.g., Lindberg 2009;Kocot et al 2020;Ponder et al 2020).…”
Section: Systematic Palaeontologymentioning
confidence: 99%
“…Muscle scars are grouped into a horseshoe-shape on the dorsal surface; the apex lies outside of this ring in some forms and may overhang the anterior shell margin; in other forms, the apex is sub-central in position. Peel (1991b) recognised three orders, reflecting three different morphological groups, the Tryblidiida Lemche 1957 typically with a pilinaform shell, the Cyrtonellida Horný, 1963 with a planispirally coiled shell, and the Hypseloconida Peel 1991b with a tall cone-shaped shell. The Tergomya is equivalent to the sub-class Tergomya of Horný (1965a, b) and is also very similar to the Tryblidiida of Wingstrand (1985); Tryblidia is broadly used interchangeably with Monoplacophora in neontological usage (e.g., Lindberg 2009;Kocot et al 2020;Ponder et al 2020).…”
Section: Systematic Palaeontologymentioning
confidence: 99%
“…The rotation hypothesis became entrenched during a time when there were no data that might contradict the assumption of a posterior mantle cavity within a gastropod progenitor, but neither was there strong independent evidence to support this assumption (no unambiguous fossil evidence, no plausible molluscan sister group with a mantle cavity confined to the posterior aspect). Subsequently, living tryblidiid monoplacophorans were discovered (Lemche 1957) and were placed as the most basal lineage of conchiferan mollusks with extant descendants, although Peel (1991) has suggested that monoplacophorans are a polyphyletic assemblage. The mantle cavity of tryblidiids is in the form of elongate lateral clefts running down each side of the foot and uniting at the posterior end.…”
Section: Torsion As a "Grand Controversy"mentioning
confidence: 99%
“…Since the discovery of Neopilina, a living creature, in 1957, it has been involved in research on the evolution of molluscs. The helcionelloids are the earliest molluscs in the Phanerozoic, but there are many concerns about their systematic position (Peel, 1991a;Geyer, 1994;Runnegar, 1996;Skovsted, 2004;Geyer et al, 2019). Most of these univalve molluscs, whose shells were not distorted in the early Cambrian, were originally classified as Monoplacophora (Yu, 1979(Yu, , 1981Jiang, 1980;Mao et al, 1993;Feng et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Peel (1991a, b) classified most of the groups of univalve molluscs whose shells were not distorted as helcionelloid. Peel (1991a) thought that the helcionelloid represented the main pedigree of univalve molluscs distinct from Tergomya, so established a new class Helcionelloida.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation